Real‐world clinical and virological outcomes in a retrospective multiethnic cohort study of 341 untreated and tenofovir disoproxil fumarate‐treated chronic hepatitis B pregnant patients in North America. Issue 11 (27th October 2020) - Samadi Kochaksaraei, Golasa; Castillo, Eliana; Sadler, Matthew D.; Seow, Cynthia H.‐T.; Barkema, Herman W.; Martin, Steven R.; Israelson, Heidi; Pinto, Jacqueline; Williams, Sarah; Aspinall, AIexander I.; Stinton, Laura M.; Borman, Meredith A.; et al.
Summary: Background: There are limited long‐term data on outcomes of chronic hepatitis B (CHB) in untreated and tenofovir disoproxil fumarate (TDF)‐treated women during pregnancy. Aims: To assess clinical outcomes in a multiethnic cohort of patients during pregnancy and post‐partum in a low HBV endemic region. Methods: Retrospective real‐world study of women with CHB (treated or untreated with TDF) from 2011 to 2019; data including ALT, HBV DNA, HBeAg and liver stiffness measurement were collected during pregnancy and post‐partum. Results: In 341 women (446 pregnancies) followed for a median of 33 months (IQR: 26.7‐39.5) post‐partum, 19% (65/341) received TDF (11 initiated pre‐pregnancy, 53 for mother‐to‐child transmission (MTCT) prevention). During follow‐up, 72/341 had subsequent pregnancy, including 18/53 on TDF for MTCT risk, of whom 7/18 were re‐treated. In all TDF‐treated women, HBV DNA declined but rebounded after TDF withdrawal (median baseline, near birth and early follow‐up levels were 7.2, 3.0 and 5.5 log IU/mL respectively [ P < 0.01]). In HBeAg+ patients (65/341) ALT flares were more common ( P = 0.03), especially for those who stopped TDF post‐partum, requiring re‐treatment in 21% (11/53). In comparison, 54% (116/215) of untreated women had a post‐partum ALT flare; one with fulminant hepatitis underwent transplant 13 months post‐partum. HBsAg clearance occurred in 2.6% (9/341, 3/9 HBeAg+, 2/9 TDF treated) at median 30 months (IQR: 23‐40) and 37% (24/65) of HBeAg+ patients had HBeAg loss at median 17 months (IQR: 12‐26) post‐partum. Conclusions: Post‐partum ALT flares were common, especially after TDF withdrawal. Overall, 37% achieved HBeAg clearance and 2.9% had HBsAg loss during long‐term follow‐up.